Workplace bullying and absenteeism: The mediating roles of poor health and work engagement. (30th May 2017) - Magee, Christopher; Gordon, Ross; Robinson, Laura; Caputi, Peter; Oades, Lindsay
Abstract: Workplace bullying is a major problem that affects the well‐being and productivity of employees. Some previous studies have found that workplace bullying is associated with absenteeism, which is a major contributor to lost workplace productivity. However, a comprehensive understanding of how different workplace bullying experiences are associated with absenteeism is currently lacking. In particular no previous studies have examined potential mediators of these relationships. The present article aimed to provide new insights into the relationship between workplace bullying and absenteeism. In a 12‐month prospective study of 500 Australian employees, we identified 5 distinct subtypes of workplace bullying experiences using a person‐centred approach. These bullying subtypes were found to be associated with absenteeism via health impairment and lower work engagement. The findings can be used to inform HR strategies to prevent and manage workplace bullying.